Β-Adrenoceptor regulation of metabolism in U937 derived macrophages. (8th June 2021) - Peterson, Amanda L.; Siddiqui, Ghizal; Sloan, Erica K.; Creek, Darren J.
Abstract : Proteomics and metabolomics reveal a shifted metabolism to support elevated ROS and cytoskeletal protein changes in β-adrenergic stimulated macrophages. Abstract : Macrophages have important roles in the immune system including clearing pathogens and wound healing. Metabolic phenotypes in macrophages have been associated with functional phenotypes, where pro-inflammatory macrophages have an increased rate of glycolysis and anti-inflammatory macrophages primarily use oxidative phosphorylation. β-adrenoceptor (βAR) signalling in macrophages has been implicated in disease states such as cancer, atherosclerosis and rheumatoid arthritis. The impact of βAR signalling on macrophage metabolism has not been defined. Using metabolomics and proteomics, we describe the impact of βAR signalling on macrophages treated with isoprenaline. We found that βAR signalling alters proteins involved in cytoskeletal rearrangement and redox homeostasis of the cell. We showed that βAR signalling in macrophages shifts glucose metabolism from glycolysis towards the tricarboxylic acid cycle and pentose phosphate pathways. We also show that βAR signalling perturbs purine metabolism by accumulating adenylate and guanylate pools. Taken together, these results indicate that βAR signalling shifts metabolism to support redox processes and upregulates proteins involved in cytoskeletal changes, which may contribute to βAR effects on macrophage function.